The Regulatory Genome: Gene Regulatory Networks in Development and Evolution - Eric H Davidson (Academic Press, 2006)
Explains the control of animal development in terms of structure/function relations of inherited regulatory DNA sequence, and the emergent properties of the gene regulatory networks composed of these sequences. New insights into the mechanisms of body plan evolution are derived from considerations of the consequences of change in developmental gene regulatory networks. Examples of crucial evidence underscore each major concept.